2019
DOI: 10.5562/cca3375
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral Analysis, Molecular Docking and Biological Evaluation of Cyclohepta[b]indole Derivatives

Abstract: A new series of specifically substituted cyclohepta[b]indole derivatives from the precursor thiophen-2-ylmethylene has been synthesized. The structures of synthesized derivatives were established by spectral and elemental analyses. The docking studies with protein kinase CK2 was performed, derivative 6c exhibited the most excellent glide and E model score of –7.61 and –58.27, respectively. In-vitro anticancer activity against cervical cancer cell line (HeLa) was studied. The IC50 values were compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Four series of indole–thiophene hybrids 52–55 (MIC: 39.5–1,957.1 μg/ml) were active against the majority of the tested B. subtilis , S. aureus , E. coli , P. vulgaris , S. typhi , P. aureus , and K. pneumoniae , and most of them (MIC: 89.5–799.7 μg/ml) were not inferior to norfloxacin (MIC: 392.3–743.4 μg/ml) against E. coli , P. vulgaris , S. typhi , and K. pneumoniae . [ 122 ] The SAR demonstrated that the introduction of pyrazole, isoxazole, and pyrimidine moieties between indole and thiophene moieties had little impact on the activity, whereas incorporation of the electron‐withdrawing group at the C‐5 position of indole moiety could boost up the activity to some extent.…”
Section: Indole/isatin–pyrrole/furan/thiophene Hybridsmentioning
confidence: 99%
“…Four series of indole–thiophene hybrids 52–55 (MIC: 39.5–1,957.1 μg/ml) were active against the majority of the tested B. subtilis , S. aureus , E. coli , P. vulgaris , S. typhi , P. aureus , and K. pneumoniae , and most of them (MIC: 89.5–799.7 μg/ml) were not inferior to norfloxacin (MIC: 392.3–743.4 μg/ml) against E. coli , P. vulgaris , S. typhi , and K. pneumoniae . [ 122 ] The SAR demonstrated that the introduction of pyrazole, isoxazole, and pyrimidine moieties between indole and thiophene moieties had little impact on the activity, whereas incorporation of the electron‐withdrawing group at the C‐5 position of indole moiety could boost up the activity to some extent.…”
Section: Indole/isatin–pyrrole/furan/thiophene Hybridsmentioning
confidence: 99%
“…Benzofused heterocycles, such as indole and benzofuran, have gained privileged recognition in drug discovery as important skeletal backbones of biologically active molecules, including naturally occurring alkaloids . In recent years, cyclohepta­[ b ]­indole and cyclohepta­[ b ]­benzofuran motifs have formed the basic skeletons for several naturally occurring alkaloids with a broad spectrum of therapeutic applications, drawing on antitumor, antibiotic, and anti-inflammatory properties (Scheme a) . The generation of a new functional framework is highly desired in next-generation drug discovery, yet it is always challenging.…”
mentioning
confidence: 99%